The Influence of Job Training, Financial Compensation, and Career Development on Employee Performance PT Ungaran Sari Garment Ungaran Branch - Annisa Himatul Maulidya; Ninik Dwi Atmini; Adji Seputro (Proceeding of the International Conference on Management, Entrepreneurship, and Business, 2024)
His study aims to (1) To know and explain the effect of job training on employee performance of PT Ungaran Sari Garment Ungaran Branch, (2) To know and explain the effect of financial compensation on employee performance of PT Ungaran Sari Garment Ungaran Branch, (3) To know and explain the effect of career development on employee performance of PT Ungaran Sari Garment Ungaran Branch, (4) To know and explain the effect of job training, financial compensation, and career development on employee performance of PT Ungaran Sari Garment Ungaran Branch.The method used in this research is quantitative research method. The conclusions of this study are: (1) Job training has a positive and significant effect on employee performance of PT Ungaran Sari Garment Ungaran Branch, (2) Financial compensation has a positive and insignificant effect on employee performance of PT Ungaran Sari Garment Ungaran Branch, (3) Career development has a positive and significant effect on employee performance of PT Ungaran Sari Garment Ungaran Branch, (4) Job training, financial compensation, career development affect employee performance of PT Ungaran Sari Garment Ungaran Branch